2019
DOI: 10.1002/app.48735
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating a partial wetting structure for improving the toughness of intumescent flame‐retardant HDPE

Abstract: Elastomer always exhibited poor efficiency for toughening flame-retardant polymer. In intumescent flameretardant HDPE, a novel multi-steps processing method was employed by Chang Lu and colleagues, to fabricate a partial wetting structure in which LLDPE-g-MAH phase with the sphere was dispersed at the interface. The partial wetting structure caused a remarkable improvement of the toughness of flameretardant HDPE with 2 wt% LLDPE-g-MAH. Its elongation at break and notched impact strength were 43% and 270% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…From Figure 10a,d, it can be seen that pure LDPE and LDPE/MCA composite completely decompose during combustion and basically produce no residue, which explains why the two samples will release a lot of heat, smoke and toxic gases during combustion. When MHPA is added, LDPE/MHPA composites produce obvious residues after combustion, but these residues do not form a stable structure, and there are obvious cracks and voids on the surface, which means that the flame is very easy to penetrate into the interior during combustion, and the damaged carbon layer is also more likely to cause secondary combustion, which is consistent with the change rules of curves such as THR and TSP 29 . In addition, it can be seen from Figure 10e that only adding MHPA cannot produce expansion effect, so it is difficult to isolate the external flame and the distance between combustible gas and internal combustible, thus it is difficult to achieve thermal insulation and flame retardant effect.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…From Figure 10a,d, it can be seen that pure LDPE and LDPE/MCA composite completely decompose during combustion and basically produce no residue, which explains why the two samples will release a lot of heat, smoke and toxic gases during combustion. When MHPA is added, LDPE/MHPA composites produce obvious residues after combustion, but these residues do not form a stable structure, and there are obvious cracks and voids on the surface, which means that the flame is very easy to penetrate into the interior during combustion, and the damaged carbon layer is also more likely to cause secondary combustion, which is consistent with the change rules of curves such as THR and TSP 29 . In addition, it can be seen from Figure 10e that only adding MHPA cannot produce expansion effect, so it is difficult to isolate the external flame and the distance between combustible gas and internal combustible, thus it is difficult to achieve thermal insulation and flame retardant effect.…”
Section: Resultssupporting
confidence: 67%
“…After adding MCA, the internal structure of LDPE/MHPA/MCA composite changes significantly. From Figure 4c, it can be seen that many small particles appear on the fracture surface of LDPE/MHPA/MCA composite, and obvious cracks appear at the junction of these particles and LDPE, which indicates that the compatibility between MCA and LDPE is poor, forming an obvious island structure 29 . MCA is an inorganic and organic LDPE with poor compatibility, which causes this phenomenon.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous research, some additives 23 showed promising flame-retardancy while mechanical properties of composites such as elongation at break were severely influenced. 3,24,25 It was due to the wide difference between the structure of the polymer and its flameretardant additives. Based on this situation, herein, we investigated a novel method in which the flame-retardant group was grafted directly to the polymer and then mixed it with the pure high density polyethylene (HDPE) matrix at the commonly used percent of 15% in industry, expecting an enhancement in the compatibility between them.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the hotspots in the field of inorganic phosphorus flame retardants. [19][20][21] However, the compatibility between IFR and polymer is poor, which makes the mechanical properties and flame retardancy of polymer decline. Moreover, the IFR is easy to absorb moisture, which will result in the water resistance decrease of flame retardant polymer.…”
Section: Introductionmentioning
confidence: 99%